SISTEM MONITORING DETAK JANTUNG DAN TEKANAN DARAH PADA SESEORANG YANG BEGADANG - FIRMANSYAH, MUHAMAD (Politeknik Negeri Indramayu, 2025)
Staying up late has become a popular trend among Generation Z; however, this activity carries significant health risks such as anemia, stroke, and even death. This study aims to design a monitoring device for heart rate and blood pressure for individuals who stay up late. The research employs a qualitative method with a questionnaire instrument distributed via Google Forms. Data collected from 27 respondents indicate that the majority sleep less than 4 hours and require a monitoring device. The device designed is IoT-based, using piezoresistive and photoplethysmography (PPG) sensors, along with a Raspberry Pi for health monitoring. The conclusion shows a significant need for this device among respondents who stay up late. Recommendations are provided for further development of the device based on the main components identified in this study.